Reflective Practices in Inquiry Learning: Its Effectiveness in Training Pre-Service Teachers' Critical Thinking Viewed from Cognitive Styles - Verawati, N. N. S. P.; Hikmawati, H.; Prayogi, S.; Bilad, M. R. (Jurnal Pendidikan IPA Indonesia, 2021)
This study aims to evaluate the effectiveness of reflective practices in inquiry learning to train pre-service teachers' critical thinking skills viewed from cognitive styles. The quasi-experimental design was conducted with two sample groups given the same treatment at the pretest, reflective-inquiry practice learning, and posttest. Before the pretest, each sample was given GEFT (Group Embedded Figures Test) to determine the sample of the FI (field-independent) or FD (field dependent) cognitive style. Two sample groups were pre-service physics teachers (PPT) at two different universities in Mataram, Indonesia. The measurement of critical thinking employed essay tests. Critical thinking skills data were analyzed descriptively (mean difference scores of pretest-posttest and N-gain analysis) and statistically (independent sample t-test) employing SPSS software. The effectiveness of reflective inquiry learning is measured by increasing critical thinking scores where the minimum posttest has the "critical" criteria. The study results indicated that the tendency of cognitive style FI was more dominant than FD. The critical thinking measurement showed that each FD/FI group was categorized as "critical," and the increase of critical thinking scores in the two groups was categorized as a "moderate" category. In line with this, statistical analysis (hypothesis testing at a significance level of 0.05) showed no difference in the increase of critical thinking scores between PPT belonging to FD and FI. This study showed that the reflective practice in inquiry learning effectively improved the pre-service teachers' critical thinking skills with the FD and FI cognitive styles. Reflective practices are a new way of inquiry learning to train critical thinking and can be used as a reference for its structured implementation in regular lectures.